One Wire is Enough - Bank, Michael (European Journal of Applied Sciences, 2022)
Is showed that any method for transmitting electrical energy one can transform at one wire method. In comparison with three phase system this method has several important advantages. Is showed also that transform to one wire system and come back is possible and useful. Obviously that transition to one wire systems can influence at all electrical system in globe.